On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae) - Mirza, Zeeshan A.; Varma, Vishal; Campbell, Patrick D (Zootaxa, 2020)
Sinomicrurus macclellandi (Reinhardt, 1844) is a species of coral snakes distributed across the forests of Southeast Asia and the Himalayas. The species exhibits distinct forms across its range, and it has been classified into four subspecies. Calliophis macclellandi nigriventer Wall, 1908 a population from Western Himalayas, which was described as a variety, has not been attended to until now. Our study of a recently collected specimen from near Solan, Himachal Pradesh, India and existing museum material has allowed us to assess the validity of this population based on molecular and morphological data and has given us enough evidence to suggest its elevation to a species rank. Sinomicrurus nigriventer comb. nov. was found to be embedded within a clade comprising S. peinani, but not S. macclellandi s. l., with a genetic distance of 7–16% from its congeners. Morphologically, it differs from its congeners in having a reddish brown dorsum and a mid-dorsal black vertebral strip extending from the nape to the vent and with three thin bands on the tail, belly white with black smear up to the vent, tail dorsum with a few band-like blotches, and males with 230–235 ventral scales.